Pendidikan Akidah dalam Surah Mu'awwidzatain - Karolina, Asri; Arcanita, Rafia; Sari, Riri Purnama; Idris, Muhammad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Akidah Education in Surah MuawwidzatainThis research is motivated by the fact that there are still many Muslims who do not fully understand the issue of faith and only follow the culture of their ancestors or customs that have existed since ancient times. The purpose of this study is to analyze the creed education contained in the Surah Mu'awiidzatain. This study uses a type of library research using a thematic interpretation approach. The method used is the method of "thematic interpretation per letter". It is said to be a per-surah thematic approach, because specifically this research will examine Surat al-Falaq and Surat an-Naas in depth with a focus on creed education. The data sources used in the research are primary sources in the form of the Qur'an, books of interpretation. While secondary or supporting data are in the form of books related to the Aqeedah, books related to the virtues of Surah Al-Falaq and Surah An-Naas. Data collection techniques by collecting literature, classifying, citing, confirming and grouping. Data analysis technique uses content analysis technique. The results of this study are in the Surah Al-Falaq in the first verse, namely Rabb (Qul a'udzuu birabbil falaq) which shows the monotheism of rububiyyah. Whereas in Surah An-Naas in verses 1-3, namely Rabb (Rabbinnaas), Malik (Malikinnaas), and Illah (Ilahinnaas) which show monotheism rububiyyah, mulkiyyah, uluhiyyah.